Perbedaan tingkat kualitas dokumentasi proses keperawatan sebelum dan sesudah penerapan NANDA-I, NIC, dan NOC - Efendy, Mohamad Asa'ad; Purwandari, Retno (Jurnal Keperawatan Soedirman, 2012)
Improving the quality of nursing can be obtained if the nurses were able to carry out nursing care standards, ranging from assessment through the following evaluation with documentation. Standardized language in describing the problems of patients is needed. Standardization of classification in nursing care is very important. The purpose of research are identifying the differences between the quality of nursing documentation before and after implementation of NANDA-I, NIC, and NOC in a hospital Anthurium PTPN X Jember. The study used a Quasi Experiment Design in the form of One Group Pretest-posttest. Sampling was carried out with total sampling method. Based on Wilcoxon Signed Rank Test, showed p value is 0.000, Research shows that there are differences in the level of quality documentation before and after implementation of standardized nursing language using NANDA-I, NIC, and NOC. The quality of the documentation before applying NANDA-I, NIC, and NOC mostly medium category (89.3%). Quality of documentation after implementation of NANDA-I, NIC, and NOC are good category (57.1%). Implementation of NANDA-I, NIC, and NOC can improve the quality of nursing documentation